Effectiveness of High Protein Supplementary Feeding on The Nutritional Status of Toddler With Wasting Risk - Yustin Ari Prihandini; Cast Torizellia; Nurfitriliani Nurfitriliani (Jurnal Berkala Kesehatan, 2022)
Toddlers in South Kalimantan who experience nutritional problems on indicators of Weight/Height, namely underweight category, at a prevalence of 5.5% above national figure of 3.9%. Data from Guntung Payung Health Center in showed there 38% of under-fives with underweight nutritional status and 9% of very thin nutritional status. One of preventive measures for undernourished toddlers is provision of supplementary food containing high protein. Research sample was 38 toddlers with a history of getting supplementary food High Protein for 3 months selected using purposive sampling method. Nutritional status of children under five was obtained using anthropometric method. BB/TB was used in assessing nutritional status with target of wasting toddlers. Research method using cross-sectional with statistical test using paired t-test with a significance level of <0.05. The results showed an increase in percentage of children under five with normal nutritional status from 65.8% to 68.4%. After not receiving high protein supplementary food, percentage of children under five with normal nutritional status decreased to 63.2%. There was no significant difference in nutritional status of children under five years old based on BB/TB. In addition, there’s no difference between nutritional status of children under five after implementation of supplementary food Recovery and during study.